A Survey on How College Students in a Statistical Literacy Course Apply Statistics Terms to People - Lawrence M. Lesser; Martin Santos (Journal of Statistics and Data Science Education, 2024)
AbstractAn anonymous survey was given to n = 73 students in an asynchronous online statistical literacy course at a mid-sized Hispanic Serving Institution. Informed by teaching experience, literature on lexical ambiguity, and everyday usage of statistics words and phrases, the first author designed the survey to yield insight into how students view phrases such as “average person,” “random person,” and “outlier person,” and to explore possible connections or patterns with such phrases. Findings suggest that students view phrases such as “random person” in a way much further from standard usage than they do phrases such as “anonymous person.” Considerations such as diversity, agency, and variable identification are identified as possibly affecting usage and meriting further investigation. Recommendations for teaching and future research are provided. Supplementary materials for this article are available online.